User Interface and User Experience Design for Vidyanusa on Android Mobile Phones Using an Evaluation Framework - Aditya Pratama (West Science Information System and Technology, 2024)
This research will evaluate the User Interface and User Experience (UI/UX) of Vidyanusa for Android mobile phones. User Experience will be measured using sub-variables such as attractiveness, agility, efficiency, dependability, stimulation, and novelty. The object of this research is User Experience. The results of this research will be used to evaluate Vidyanusa's Android mobile product to achieve a product that is suitable for users at the junior high school level. User experience testing on the Vidyanusa mobile application uses evaluation methods with query techniques. Evaluation is a test of the level of system usability and functionality that is carried out in the laboratory, in the field, or in collaboration with users. What is evaluated is the design and implementation, and the technique used is the evaluation technique with the User Experience Questionnaire. The results of the user experience testing of the Vidyanusa mobile application tend to be negative on the points of attractiveness, perspicuity, efficiency, dependability, and novelty based on the User Experience Questionnaire in the benchmark table, but positive on the point of stimulation.